Peran Dosen Fakultas Ekonomi dan Bisnis Universitas Teknologi Sumbawa dalam Peningkatan Literasi dan Inklusi Keuangan pada Masyarakat Kabupaten Sumbawa - Salam, Abdul; Abdurrahman, Abdurrahman (Universitas muhammadiyah palembang, 2020)
The purpose of this study was to identify the outcomes of higher education, in this case the University Technology of Sumbawa, because of its strategic location and positive response from the people of Sumbawa Regency, its ability to create added value and strategies for increasing public awareness of its financial future.The object of this research is the community in Sumbawa Regency with a sample size of 250 respondents. This study measures the role of Lecturers on, Financial Literacy and Inclusion.This study found that financial literacy partially affects the role of lecturers in being rejected. The financial inclusion variable has a significant effect on the role of the lecturer. Meanwhile, the variables of financial literacy and financial inclusion have a simultaneous effect on the role of lecturers.The conclusion of this research is in determining the right strategy to improve Financial Literacy and Financial Inclusion by increasing the role of Lecturers through Tri Dharma in order to create a well-lierate financial society